Speculative trade under unawareness: The infinite case - Martin Meier; Burkhard C. Schipper (University of California, Department of Economics, 2010)
We generalize the No-trade theorem for finite unawareness belief structures in Heifetz, Meier, and Schipper (2009) to the infinite case.
Keywords: C70; C72; D53; D80; D82; 330; awareness; unawareness; speculation; trade; agreement; common prior; common certainty